Hubungan antara Komunikasi Orang tua terhadap Anak dengan Temper Tantrum Anak di TK Nurul Hidayah - Mega Sukma; Rani Fitriani Arifin; Farhandka Putra (Pustaka Kesehatan, 2019)
Age 4 to 6 years is a stage referred to as pre-school age, it is a golden period of child development, related to his social and emotional development, children begin to learn to manage their emotions. The thing which is often occur in pre-school age children is disobedience and tantrum behavior (temper tantrum). Child's emotional development is influenced by changes in interaction and communication patterns in the family. Communication between parents and children is very important, as a medium for bridging fellow family members. The aim of this study was to determine the correlation between parent’s communication to children with child’s tempered tantrum. This study was quantitative with cross-sectional approach. The sample was parents (mother/father) of children who studied at the Nurul Hidayah Kindergarten. There were 58 respondents which was choosed by Stratified Random sampling technique. The results showed that the percentage of parent’s communication to children in the medium category was 31 respondents (53.4%), and children in the risk category of tempered tantrums were 34 respondents (58.6%). Analysis using the Chi-square test obtained the p value of 0.752 (p> 0.05). The conclusion of study, there was no correlation between parent’s communication to children and child’s tempered tantrum at the Nurul Hidayah Kindergarten, Simpang Empat, Tanah Bumbu in 2018. It was recommended that mothers do mentoring about all things related to child’s tempered tantrum.